2020
DOI: 10.1177/0958305x20937686
|View full text |Cite
|
Sign up to set email alerts
|

The impact of international sanctions on energy security

Abstract: This study first investigates different types of sanctions on energy security by employing data from a panel of target countries covering the period 1996–2014 and using the panel fixed effect model. Our evidence indicates that international sanctions do significantly negatively influence the energy security of target countries in some cases. Specifically, unilateral sanctions, U.S. sanctions, economic sanctions, and the intensity of sanctions have a significantly negative impact on energy security. However, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…Huge negative shocks have devastated the corporates' innovation activities Zhao et al, 2022), management activities (Wen et al, 2020), and stock market performance (Chang et al, 2021), but corporates with better ESG/CSR performances can better control their risks and reduce the losses of investors (Broadstock et al, 2021).…”
Section: Environmental Social and Governance And Corporate Social Res...mentioning
confidence: 99%
“…Huge negative shocks have devastated the corporates' innovation activities Zhao et al, 2022), management activities (Wen et al, 2020), and stock market performance (Chang et al, 2021), but corporates with better ESG/CSR performances can better control their risks and reduce the losses of investors (Broadstock et al, 2021).…”
Section: Environmental Social and Governance And Corporate Social Res...mentioning
confidence: 99%
“…Zhao et al ( 2021 ) found that natural catastrophes and man-made disasters have distinct impacts on the insurance industry, because they need to pay out a lot of insurance coverage. In addition, disasters, both natural and man-made, hugely impact the victims themselves and financial institutions (Wen et al 2020 ).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…In other words, energy security is not only an economic issue, but also a political, military, and strategic issue (Le & Nguyen, 2019). More and more studies are focusing on the significant variation in energy security across countries and the determinants of energy security, with some of the determinants found being economic sanctions, extreme events, and economic development (Chen et al, 2019;Wen et al, 2021). However, few, if any, empirical studies explore the impact of epidemics on energy security.…”
Section: Introductionmentioning
confidence: 99%